BEN DAN BUN EPISODE MERINGKUS PENGEDAR NARKOBA DI SEKOLAH: DALAAM KARYA KOMIK - Ade Moussadecq; Achyar Sikumbang; Suib Awrus (Universitas Negeri Padang, 2012)
Abstract The porpuse of make comic is: (1) Giving message to publicsher about adoselent problem because the drug usely. (2) Train for making a comic which the do it among scenario of reality and imajinasition. (3) Giving a referensition about visual communication like a comic.To make this last project real were some proses, its are: First Starter, looking for art ideas from referensition about adoselent’s problems. Second Elaboration, data analisist. Third Sintetion, make a schedule from this last project. Four Consep realization, make a skenario. Fife Finishing, continue the scenario to become a comic works. The description of this last project is Ben and Bun are comic which up to date about adoselent problems in drug usesly case and circle with drug user etc which are 28 page and make with comedy inside it. Kata kunci: Remaja, Narkoba, Komik